2001
DOI: 10.1148/radiol.2203001418
|View full text |Cite
|
Sign up to set email alerts
|

Aortic and Arterial Aneurysms in Behçet Disease: Management with Stent-Grafts—Initial Experience

Abstract: The findings in this initial experience suggest that stent-graft insertion may be a safe and effective alternative to surgical treatment of aortic and arterial aneurysms in patients with Behçet disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 15 publications
3
76
0
5
Order By: Relevance
“…In recent years, there have been a number of reports regarding the use of stent-graft treatment in patients with Behçet's disease as a minimally invasive treatment as an alternative to the conventional surgical method consisting of the graft replacement. [5][6][7][8] However, many questions remain unsolved regarding its long-term outcome. Park, et al, 8) reported that the recurrence of an aneurysm at the distal part of the stent graft was found in 1 patient in whom stent grafts were placed in nine different locations for the treatment of aneurysms due to Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been a number of reports regarding the use of stent-graft treatment in patients with Behçet's disease as a minimally invasive treatment as an alternative to the conventional surgical method consisting of the graft replacement. [5][6][7][8] However, many questions remain unsolved regarding its long-term outcome. Park, et al, 8) reported that the recurrence of an aneurysm at the distal part of the stent graft was found in 1 patient in whom stent grafts were placed in nine different locations for the treatment of aneurysms due to Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Venous aneurysms in BD are due to presence of a predisposing factor such as trauma or other inflammatory disorders [18]. Arterial manifestations occur less frequently comparing with venous involvement and constitute 12% of vascular complications [12,19,20]. Aneurysm of the thoracic aorta, pulmonary artery and major branches occur in 65% of patients and occlusion in 35% [20,21].…”
Section: Thoracic Vascular System Involvementmentioning
confidence: 99%
“…Arterial manifestations occur less frequently comparing with venous involvement and constitute 12% of vascular complications [12,19,20]. Aneurysm of the thoracic aorta, pulmonary artery and major branches occur in 65% of patients and occlusion in 35% [20,21]. BD is one of the most common causes of pulmonary artery aneurysms (Figures 3 and 4).…”
Section: Thoracic Vascular System Involvementmentioning
confidence: 99%
“…3 Park et al treated seven patients with aortic aneurysms using endovascular surgery and observed one case of degeneration of the distal endoprosthesis anchor site. 10 Nitecki et al…”
mentioning
confidence: 99%